Evaluation of Anticancer activity of Silver Nanoparticles on the A549 Human lung carcinoma cell lines through Alamar Blue Assay - Sharma, Nikita (Bio Protoc, 2019)
Silver nanoparticles have been widely studied to possess antimicrobial as well as anticancer activity, and have found its applications in various fields including pharmaceutical industry, diagnostics, drug delivery, food industry, and others. For this purpose, several cell proliferation assays are widely used for the evaluation of anticancer activity of synthetic compounds as well as natural plant extracts. In general, a compound is said to possess an anticancer activity if it prevents the cancer cells to grow and divide actively, and indirectly activates the generic program of cell death. In this protocol, Alamar blue and MTT assay are described for the analysis of metabolic function and health of the cell. These procedures are generally used for the endpoint analysis. A549 cells are seeded in a 96-well plate, and after the adherence of the cells, they are treated with different concentrations of silver nanoparticles. Followed by 24 h of incubation, colorimetric dyes are added to the wells, and the absorbance is recorded to quantify the percentage cytotoxicity in the sample wells.